‘Goodbye it's 1987’: generation of the new - Matless, David (Wiley, 2016)
This paper reflects on Cosgrove and Jackson's (1987) Area paper ‘New directions in cultural geography’ (Area, 19, 95–101), discussing its place within British geography in the 1980s, the associated conferences organised through the Institute of British Geographers, the continuing resonance of its themes and the nature of a ‘classic’ paper. Historical analysis is combined with personal memory to consider the paper's role in generating a ‘new’ cultural geography.